An Analysis of India's Export Performance with China. (August 2015) - Singla, Surinder Kumar
India and China are two rapidly emerging economies in the world. With their high growth rates and huge markets, these two Asian giants have attracted the attention of international business mangers to take a fresh look at the rapidly emerging opportunities in the two countries. Today, India–China relations are conspicuous by the fast rise of their merchandise trade, which has already crossed US$ 42 billion in 2009–2010. China has already become India's second largest trade partner only after UAE. Besides this, China has also become one of the most favourite destinations for Indian exporters. China's share in India's global exports has increased rapidly from just 0.10 per cent in 1990–1991 to 6.47 per cent in 2009–2010. However, this growth of Indian exports to China has not been equally distributed over various commodity groups. In fact, Indian exports to China are mainly dominated by natural resource-based raw materials or semi-manufactured products which are not considered to be healthy from the Indian point of view. Hence, there is an urgent need to add some technologically advanced products in the export basket to China. According to the need of the time, the present study examines the various trends that occurred in growth and structure of Indian exports to China during the last two decades.